Synthesis of Icariin-Zinc and its Protective Effect on Exercise Fatigue and Reproductive System Related Glands in Male Rats - Zhang, Juntao; Zhang, Chao; Liu, Aifeng; Ji, Qiang; Ren, Lixia; Ma, Chuanrui; Zhang, Hengyu; Wu, Chaochao; Zhang, Donglin; Shang, Man; He, Feng (Frontiers in Pharmacology, 2021)
Background：Icariin plays a protective role in the treatment of exercise fatigue. Zinc plays an important role in the reproductive system. Therefore, we synthesized Icariin-Zinc by chemical technique. we verified its protective effect on exercise fatigue and reproductive system through animal experiments. Methods：Icariin zinc was prepared by the reaction of icariin carbonyl and zinc ion (molar ratio 1:3).The molecular formula and structural formula of icariin zinc were identified and tested. 56 rats selected by swimming training were randomly divided into six groups: static control group, exercise control group, Icariin group, gluconate zinc group (G-Zn group), Icariin glucose zinc, Icariin zinc exercise group. The dosage according to 1ml/100g, Gavage daily by NS, NS, 45mg/kg icariin, 110mg/kg Gluconate Zinc, Icariin glucose zinc (45 mg/kg Icariin and 110 mg/kg Gluconate Zinc), 60mg/kg icariin zinc and 180mg/kg icariin zinc. After 3 weeks of gavage, we conducted 6 weeks of exhaustive swimming training. During the experiment, the test indexes, such as exhaustion time of rats and the body weight, were evaluated after the last training assay. The seminal vesicle gland, testis and prostate gland were weighed, respectively, and their indexes were calculated. The contents of testosterone in plasma and glycogen in liver and muscle homogenate were detected by ELISA assay. Results：the exhaustive swimming time of L-E group and H-E group was significantly longer(p<0.01); Icariin-Zinc significantly increased the exhaustive swimming time of rats. the plasma testosterone content of L-E and H-E group increased significantly(P<0.05); Compared with the exercise control group and G-Zn group, the plasma testosterone content of H-E group also increased significantly(P<0.01); Icariin-Zinc significantly increased the serum levels of testosterone in rats.Compared with the control group, the muscle glycogen reserves of each group decreased, indicating that the muscle glycogen reserves of rats decreased after swimming; Compared with the static control group and the exercise control group, the testicle weight of rats in the administration group increased slightly. Conclusion：Icariin-Zinc can significantly prolong the exhausted swimming time, improve the exercise ability of rats, and increase the content of testosterone in plasma, the beneficial effect of Icariin-Zinc on glycogen content, testis index and other reproductive system glands is dose-dependent.